Spacecraft technology - Mason, John (John W.) (New York : Bookwright Press, 1990)
An introduction to space technology, discussing the principles of rockets, various types of satellites, travel in the solar system, and space stations.
Includes index.
Includes bibliographical references.
Keywords: Astronautics -- Juvenile literature; Astronautics